The Influence of Visual Distraction on Awareness Test - Yen-Ting Lo, Rachel; Suen, Mein-Woei (Scientific Research, 2014)
In everyday situation, there are so many events happening around our lives. Although human beings are capable of perceiving many events happening at the same time, it is not possible for individuals to pay attention to every little detail that they face in this complex environment. In this study, the effect of visual distraction on awareness test was evaluated. The hypothesis was that the presence of visual distraction via laser lights will lower the score on awareness test, whereas a higher score on awareness test would occur when laser lights were absent. The study evaluated 3 male and 14 female university undergraduate students’ performance on awareness test and predicted that their performance would be affected by distractions. In the end, data analysis obtained a supportive result to the hypothesis. The study brought up more significant issues between distraction and awareness which also drew more interests for researchers in different fields.
Keywords: Distraction; Awareness; Perception